Mercury Exposure and Associations with Hyperlipidemia and Elevated Liver Enzymes: A Nationwide Cross-Sectional Survey - Seungho Lee; Sung-Ran Cho; Inchul Jeong; Jae Bum Park; Mi-Yeon Shin; Sungkyoon Kim; Jin Hee Kim (Toxics, 2020)
Mercury (Hg) has obesogenic properties. However, the associated health outcomes of population-level mercury exposure were unclear. This study investigated the relationships between blood mercury levels and obesity-related outcomes such as hyperlipidemia and elevated liver enzymes. Using the second cycle of the Korean National Environmental Health Survey (n = 6454), we performed logistic regression to examine the effects of Hg on hyperlipidemia and elevated liver enzymes. The blood mercury levels were significantly higher in the hyperlipidemia group (n = 3699, male: 4.03 μg/L, female: 2.83 μg/L) compared to the non-hyperlipidemia group (n = 2755, male: 3.48 μg/L, female: 2.69 μg/L), and high blood mercury levels were associated with an 11% higher risk of hyperlipidemia. The elevated liver enzymes group had higher mean blood mercury levels (n = 1189, male: 4.38 μg/L, female: 3.25 μg/L) than the normal group (n = 5265, male: 3.64 μg/L, female: 2.70 μg/L), and elevated blood mercury was associated with a 35% higher risk of elevated liver enzymes. Moreover, the effect was constant after adjusting for personal medications. These results indicate that mercury exposure is significantly associated with hyperlipidemia and elevated liver enzymes.